Structural Design : Comparison between STAAD Pro and Manual Calculation - Abd Kadir Jalani, Muhammad Nur Hakim; Zulkiflee, Muhammad Azam Najmi; Zohan, Ahmed Naseh Rifqi; Kesot, Mohd Jahaya (Multidisciplinary Applied Research and Innovation, 2022)
Structural design is an art and science of constructing a systems that are economical, practical and resilient. In general, this project is an application of  theorectical design knowledge combined with practical skill of utilizing modern engineering tools. A structural frame is selected as design model. Engineering data partaining to design process such as type of materials, geometrical arrangement adnd sizing were feeded into STAAD Pro. Analysis was run according to prevalent code of practice. The output generated is feed into AUTOCAD to produce working engineering drawing. To comply with standard engineering practice, output from any automated design software such as STAAD Pro is counter check with manual calculation. Outcome of this project prove that both output were within reasonable engineering expectation. Using software for design process did expedite time and reduce error, but familiarity with using commands and procedures is necessary.